Partial melting of metagreywacke: a calculated mineral equilibria study - Johnson, Tim; White, R.; Powell, R. (Wiley - Blackwell, 2008)
Greywacke occurs in most regionally metamorphosed orogenic terranes, with depositional ages from Archean to recent. It is commonly the dominant siliciclastic rock type, many times more abundant than pelite. Using calculated pseudosections in the Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–O system, the partial melting of metagreywacke is investigated using several natural protolith compositions that reflect the main observed compositional variations. At conditions appropriate for regional metamorphism at mid-crustal depths (6–8 kbar), high-T subsolidus assemblages are dominated by quartz, plagioclase and biotite with minor garnet, orthoamphibole, sillimanite, muscovite and/or K-feldspar (±Fe–Ti oxides). Modelled solidus temperatures are dependent on bulk composition and vary from 640 to 690 °C. Assuming minimal melting at the H2O-saturated solidus, initial prograde anatexis at temperatures up to ~800 °C is characterized by very low melt productivity. Significant melt production in commonly occurring (intermediate) metagreywacke compositions is controlled by the breakdown of biotite and production of orthopyroxene (±K-feldspar) across multivariant fields until biotite is exhausted at 850–900 °C. Assuming some melt is retained in the source, then at temperatures beyond that of biotite stability, melt production occurs via the consumption of plagioclase, quartz and any remaining K-feldspar as the melt becomes progressively more Ca-rich and H2O-undersaturated. Melt productivity with increasing temperature across the melting interval in metagreywacke is generally gradational when compared to metapelite, which is characterized by more step-like melt production. Comparison of the calculated phase relations with experimental data shows good consistency once the latter are considered in terms of the variance of the equilibria involved. Calculations on the presumed protolith compositions of residual granulite facies metagreywacke from the Archean Ashuanipi subprovince (Quebec) show good agreement with observed phase relations. The degree of melt production and subsequent melt loss is consistent with the previously inferred petrogenesis based on geochemical mass balance. The results show that, for temperatures above 850 °C, metagreywacke is sufficiently fertile to produce large volumes of melt, the separation from source and ascent of which may result in large-scale crustal differentiation if metagreywacke is abundant.